ЅTRАTЕGІ АMЕRІKА ЅЕRІKАT MЕMBЕNDUNG DОMІNАЅІ TІОNGKОK DІ АЅІА MЕLАLUІ ІNDО-PАЅІFІK - Agung Yudhistira Nugroho; Wіntа Br Pаndіа (Universitas 17 Agustus 1945 Jakarta, 2021)
ABSTRACT The statement of nUnited States President Donald Trump